Validity and Reliability Test New Questionnaire of Knowledge, Perception, Family Support, and Adherence of Pregnant Women with Anemia Using TTD Supplement - Rizka Novia Atmadani; Dinar Famora Arum; Akrom Akrom; Siti Urbayatun (Universitas Muhammadiyah Sidoarjo, 2025)
Anemia according to WHO (World Health Organization) is defined as crucial incidence during pregnancy. In adult groups, it is common in women of reproductive age, especially in pregnant women due to iron deficiency. Pregnant women need to consume Iron Folic Acid Supplement/Tablet Tambah Darah (TTD) regularly to prevent and overcome anemia. Several factors are important to be studied in anemic pregnant women. Therefore, researchers wanted to examine the validity and reliability of the new questionnaire. The purpose of this study was to determine the validity and reliability of the questionnaire on the level of knowledge, perceived barriers, perceived benefits, and adherence in anemic pregnant women in the use of TTD. This study uses quantitative research in the form of descriptive research and uses a cross-sectional design. Using non- probability sampling with purposive sampling technique and 100 mothers. In research conducted in September 2023 showed that the validity and reliability test questionnaire on the questionnaire level of knowledge, perceived barriers, perceived benefits, family support and adherence questions are valid and also reliable with Cronbach alpha above 0.6.